DAMPAK CORPORATE SOCIAL RESPONSIBILITY (CSR) LEMBAGA PERKREDITAN DESA (LPD) TERHADAP PEMBERDAYAAN MASYARAKAT DESA ADAT GULINGAN, KECAMATAN MENGWI, KABUPATEN BADUNG - Rai Dwinta Sari, Dewa Ayu Kade; Supriliyani, Ni Wayan; Winaya, I Ketut (CITIZEN CHARTER, 2018)
ABSTRACT Corporate Social Responsibility (CSR) is social responsibility given by the institution to community for minimalize negative impact and maximize positive impact in order advance the development of village by sustainable by means of econimic, social, and circles aspect. LPD (Lembaga Perkreditan Desa) Desa Adat Gulingan as the financial institution has pakraman village already may apply Corporate Social Responsibility programme to help prosperity and community empowerment Gulingan village. The research was used by a qualitative descriptive method with data collection technique like a observation, interview, and documentation. The research measures how CSR program impact LPD Desa Adat Gulingan against community empowerment with Financial Administration Theory and discuss with Community Empowerment Concept by Narayan that based on indicator of access to information, participation, accountability, and capacity. The results of this research indicate the CSR program owned by LPD Desa Adat Gulingan already can bring positive impact to the entire community, but not already can bring community empowerment impact. Stage and level community empowerment in Gulingan village still in the beginning process to achieve the independent community. Keywords: CSR, LPD, Community Empowerment